Newton's fifth degree dilemma

Algebra Level 4

Find α 5 + β 5 + γ 5 \alpha^{5} +\beta^{5}+\gamma^{5} , if α \alpha , β \beta and γ \gamma are the roots of the equation x 3 + 3 x + 3 = 0 x^{3}+3x+3=0 .


The answer is 45.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

x 3 + 3 x + 3 = 0 x^{3} + 3x + 3 = 0
c y c l i c α = 0 , c y c l i c α β = 3 \displaystyle \sum_{cyclic} \alpha = 0 , \sum_{cyclic} \alpha\beta = 3
x 3 = 3 x 3 x^{3} = -3x - 3
x 5 = 3 x 3 3 x 2 x^{5} = -3x^{3} - 3x^{2}
x 5 = 3 ( 3 x 3 ) 3 x 2 = 9 x + 9 3 x 2 x^{5} = -3(-3x-3) - 3x^{2} = 9x + 9 - 3x^{2}
c y c l i c α 5 = 9 c y c l i c α + 9 c y c l i c 1 3 c y c l i c α 2 \displaystyle \sum_{cyclic} \alpha^{5} = 9\displaystyle \sum_{cyclic}\alpha+ 9 \sum_{cyclic} 1 - 3\sum_{cyclic} \alpha^{2}
S = 9 ( 0 ) + 9 ( 3 ) 3 ( 0 2 2 ( 3 ) ) = 27 + 18 = 45 S = 9(0) + 9(3) - 3(0^{2} -2(3)) = 27 + 18 = 45


Short and sweet :) Same way BTW.

Abdur Rehman Zahid - 5 years ago
Hung Woei Neoh
Jun 11, 2016

For easy typing purposes, let α = a , β = b \alpha = a,\;\beta=b and γ = c \gamma=c

x 3 + 3 x + 3 = 0 x^3+3x+3=0

From Vieta's formula, we know that:

a + b + c = 0 a b + a c + b c = 3 a b c = 3 a+b+c=0\\ ab+ac+bc=3\\ abc=-3

Use Newton's sums to find the value of a 5 + b 5 + c 5 a^5+b^5+c^5 :

a 2 + b 2 + c 2 = ( a + b + c ) 2 2 ( a b + a c + b c ) = 0 2 2 ( 3 ) = 6 a 3 + b 3 + c 3 = ( a + b + c ) ( a 2 + b 2 + c 2 ) ( a b + a c + b c ) ( a + b + c ) + 3 a b c = 0 ( 6 ) 3 ( 0 ) + 3 ( 3 ) = 9 a 4 + b 4 + c 4 = ( a + b + c ) ( a 3 + b 3 + c 3 ) ( a b + a c + b c ) ( a 2 + b 2 + c 2 ) + a b c ( a + b + c ) = 0 ( 9 ) 3 ( 6 ) + ( 3 ) ( 0 ) = 18 a 5 + b 5 + c 5 = ( a + b + c ) ( a 4 + b 4 + c 4 ) ( a b + a c + b c ) ( a 3 + b 3 + c 3 ) + a b c ( a 2 + b 2 + c 2 ) = 0 ( 27 ) 3 ( 9 ) + ( 3 ) ( 6 ) = 27 + 18 = 45 a^2+b^2+c^2 = (a+b+c)^2 - 2(ab+ac+bc) = 0^2 - 2(3) = -6\\ a^3+b^3+c^3 = (a+b+c)(a^2+b^2+c^2) -(ab+ac+bc)(a+b+c)+3abc = 0(-6)-3(0)+3(-3) = -9\\ a^4+b^4+c^4 = (a+b+c)(a^3+b^3+c^3) - (ab+ac+bc)(a^2+b^2+c^2) + abc(a+b+c) = 0(-9) - 3(-6)+(-3)(0) = 18\\ a^5+b^5+c^5 = (a+b+c)(a^4+b^4+c^4) - (ab+ac+bc)(a^3+b^3+c^3) +abc(a^2+b^2+c^2) = 0(27) - 3(-9)+(-3)(-6) = 27+18 = 45

α 5 + β 5 + γ 5 = 45 \implies \alpha^5+\beta^5+\gamma^5 =\boxed{45}

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...